Relationships between Inflation Rate and Market Value per Share of Commercial Banks: Evidence from Bangladesh - Chowdhury , Abu Nomaan Mohammad Minhajul Haque (Global Disclosure of Economics and Business, 2017)
The market value per share of financial institutions depends on a range of internal and macroeconomic variables. Inflation rate of a country is one of the macroeconomic variables that substantially influence the market price of share of the financial organizations. This study aimed at determining the relationship between inflation and market value per share of commercial banks in Bangladesh. Researchers used market value per share of 10 commercial banks and inflation rate for the period 2011 to 2015 as secondary data. A number of statistical tools (average, percentage change, median, maximum, minimum, standard deviation, coefficient of correlation and coefficient of determination) were used to find out the results. It was found that inflation of a country had significant positive effect on the market value per share of the selected commercial banks. JEL Classification Code: G 21